Achyranthes bidentata Polysaccharide along with Anti-IL-5 Antibody Inhibits Allergic Lung Inflammation and Airway Hyperresponsiveness Mice Induced by House Dust Mites - Jian Sun; Shiwei Sheng; Gang Zhao (International Journal of Polymer Science)
Bronchial asthma is a chronic inflammatory disease which has become prevalent worldwide. There are millions of new patients and thousands of people die from asthma. Asthma is characterized with infiltration by eosinophils in pulmonary parenchyma, high serum IgE, and cytokines like IL-4, IL-5, and IL-13 secreted by allergen-specific T helper cell-2 (Th2) cells. Products of eosinophils are considered as negative regulators that work on remodeling lung tissue, including airway thickening, fibrosis, and angiogenesis. Achyranthes bidentata polysaccharide (ABPS) is a kind of polysaccharide extracted from the dry root of Achyranthes plant Achyranthes bidentata. ABPS is reported to have multiple biological functions and acts on the human immune system. ABPS can induce production of TNF-α in macrophage, enhance the killing ability of NK cells, and promote the proliferation of B cells. Besides this, ABPS is reported that can induce apoptosis of eosinophils by upregulating the expression of proteins involved in apoptosis. In this study, we constructed chronic allergic asthma mice model induced by house dust mites (HDM) with airway hyperresponsiveness (AHR) and found that anti-IL-5 mAb and ABPS treatment can both decrease inflammatory cells infiltration especially eosinophils and decrease the level of serum IgE and HDM-specific IgG1. The level of IFN-γ is increased and AHR is improved, and a more significant phenomenon was observed in anti-IL-5 mAb and ABPS combined treatment.